Bibliometric analysis of the potential of technologies in the humanitarian supply chain (2021)
This study presents a bibliometric analysis of research on technology in the humanitarian supply chain. The methodology includes performance analysis and science mapping to explore the application of technologies in humanitarian supply chains. This paper contributes to the literature by examining the most influential authors, trends, journals, countries, institutions, and the recent humanitarian supply chain collaboration. The information presented in this research was obtained with the Scopus database. The study identified 342 documents after applying filters to screen for duplicates and manuscripts unrelated to the topic. The articles were analyzed using MS Excel and VOSviewer. The research provides an overview of state of the art showing a high collaboration between the authors Ramesh A. and Kabra C, and the most relevant institutions were the Griffith Business School and the Delft University of Technology. Journal of Humanitarian Logistics and Supply Chain Management and Journal of Disaster Research were the most productive journals. The terms analysis shows that “disasters”, “disaster prevention”, “humanitarian logistics”, and “human” are the most used keywords. The study identifies future research lines related to the interaction between critical technologies to deliver real benefits to the humanitarian supply chain. As a result, it proposes integrating the significant contributions of new technologies, such as blockchain, big data, artificial intelligence, 3D printing, virtual and augmented reality, and the social media relief phase following the disaster. It also indicates gaps in knowledge in terms of research related to human-made disasters and health emergencies.